SPATIO-TEMPORAL VARIATIONS IN POPULATION DENSITY OF TERRESTRIAL ISOPOD, Philoscia muscorum WITH REFERENCE TO SOIL EDAPHIC FACTORS AT SELECTED AREAS OF THIRUVANANTHAPURAM DISTRICT, KERALA - MANJARY, S.; SANALKUMAR, M. G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Soil is a heterogeneous habitat for diverse group of organisms. Soil fauna render diverse ecological services which are essential for soil health. The present study attempts to find out the impact of edaphic as well as chemical factors in soil on the population density of Philoscia muscorum in three areas of Thiruvananthapuram district- Nedumangad, Peppara and Bonacaud. Samples were collected using standard procedures and chemical analysis was done. Two way ANOVA and Principal Component Analysis were done as part of statistical analysis. Physico chemical parameters- gravel, silt, clay, sand, exchangeable acid, exchangeable base showed seasonal variation as well as site-wise variation while there was no significant variation- sitewise and seasonal – in organic carbon content. The chemical factors- Nitrogen, Phosphorus, Potassium, Calcium and Magnesium showed site-wise and seasonal variations. Population density was highest during post-monsoon season in all the study areas (Nedumangad 71.48±0.204, Peppara 75.68±0.458 and Bonacaud 82.08±0.329). Clay, gravel, sand, pH, exchangeable acid, Nitrogen, Phosphorus, Calcium and Magnesium are identified as the Principal Components influencing population density of Philoscia muscorum in the study areas.